Clinical Outcome of Diabetes Patients with Asthma Complications Using Corticosteroids - Setya Ningtyas, Maria Sheila; Ramatillah, Diana Laila; Farrukh, Muhammad Junaid (Journal La Medihealtico, 2024)
Diabetes and asthma is disease No infectious However prevalence his Enough big in Indonesia. Study This aim For knowing the clinical outcome of diabetes patients with complications asthma who uses corticosteroids. Study This use method cohort retrospective and prospective for 3 months. Of 150 patients , 76% were Woman with level education the most namely SMA 44%. Obtained results prevalence use corticosteroids is methylprednisolone namely 45.4% with a period of use of 6-10 years. There is no significant relationship between type corticosteroids with clinical outcomes. Can concluded that the clinical outcome of patients who lived was 96.7% and those who died namely 3.33% as well No there is significant relationship between type corticosteroids with clinical outcomes.